2013
DOI: 10.3855/jidc.2460
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methicillin-resistant Staphylococcus aureus nasal carriage in Malagasy patients

Abstract: Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of infections. It is well recognized that nasal carriage of S. aureus represents a potent and increasingly prevalent risk factor for subsequent S. aureus infection. However, in Madagascar no data exist concerning this nasal carriage of S. aureus. Methodology: Nasal swabs from 304 different patients attending the Laboratory of Training and Research in Medical Biology of Madagascar were cultured for methicillin sensitive (MSSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
(11 reference statements)
0
18
2
Order By: Relevance
“…Although the prevalence of S. aureus colonization (38.33%) in this sample is similar to world population estimate, that of MRSA colonization (25%) is higher compared to that reported from the unexposed Malagasy community (14.80%) [9]. However, this rate seems to be similar to (if not lower than) the population who is frequently in contact with animals, particularly pigs.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Although the prevalence of S. aureus colonization (38.33%) in this sample is similar to world population estimate, that of MRSA colonization (25%) is higher compared to that reported from the unexposed Malagasy community (14.80%) [9]. However, this rate seems to be similar to (if not lower than) the population who is frequently in contact with animals, particularly pigs.…”
Section: Discussioncontrasting
confidence: 38%
“…This hypothesis should be confirmed by molecular typing analysis. In comparison with MRSA isolated from potentially ill Malagasy community reported in our previous study [9], MRSA nasal strains from farmers presented similar high rates of resistance, particularly to trimethoprim-sulfamethoxazole (68.89% versus 74%), erythromycin (66.67% versus 63.5%), and tetracycline (71.11% versus 62%). This increase of drug resistance concerns antimicrobials that are frequently used in our community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result, 9.04 % (n=14)of MRSA nasal carriage is higher than those documented in Netherland and Brazil afore mentioned [4,7]. Likewise, MRSA nasal carriage of Danish veterinary practitioners (means professionally exposed to animals) was 3.9% [13] which is similar to the MRSA carriage rate in the general population (healthy individuals and outside the healthcare environment) estimated to be less than 4 % [14][15].However, this recorded rate seems to be lower compared to those reported among veterinarians from international study (12.5%) [6], from UK veterinarians (12.3%) [5] and intriguingly among unexposed Malagasy population (14.8%) [9]. In one hand, a lower rate could be comprehensive as students are considered as healthy population, with limited risk till they do frequently in touch with high risk factor area such as health and veterinarian care unit.…”
Section: Discussionmentioning
confidence: 50%
“…In parallel, cross-sectional studies of unexposed Malagasy community reported 38.16 % of S. aureusnasal carriage with 14.8 % of MRSA strains [9]. However, to the best of our knowledge, no data concerning the frequency of MRSA nasal carriage among potentially exposed Malagasy community is available yet.…”
Section: Introductionmentioning
confidence: 93%